Desain Pembangkit Listrik Tenaga Surya di Gedung Seraguna Politeknik Penerangan Indonesia Curug - Jatu Maulana Sakti; Yayuk Suprihartini; Taryana (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
Curug Indonesia Aviation Polytechnic multipurpose building is located in Tangerang, Banten, Indonesia. The multipurpose building is a supporting facility of the Curug Indonesian Aviation Polytechnic for cadet activities such as seminars, socialization, to extra-curricular activities. The load that is often used is lighting. The electricity supply for this building is still using PLN. By utilizing sunlight in Indonesia, the author designed solar power plant as an alternative energy to supply electricity for the lighting section of the Indonesian Aviation Polytechnic Curug multipurpose building. Design of solar power plant was tested using the PVsyst application to determine the average daily energy produced by solar panels. The results of these tests are worth 50.18 kWH/day. If the solar power plant produces more energy than the load to be supplied, it will be directly transferred to the loads connected to the substation II whose value will be monitored by KWH EXIM